The Effect of Islamic Leadership on Organizational Commitment Through Organizational Culture as Mediating Variable - Nima, Jazilah Lailatun; Maksum, Ikhsan (Manunggal Halim Jaya, 2025)
This research explores the influence of Islamic leadership on organizational commitment, with organizational culture serving as a mediating variable among employees. Utilizing a quantitative method, the study applied a saturated sampling technique and involved 61 respondents. Data was gathered through questionnaires distributed via Google Forms. The results demonstrate that Islamic leadership strongly and positively impacts organizational commitment. Leaders who embody Islamic values—trustworthiness, perseverance, and responsibility—encourage more extraordinary team member dedication. Furthermore, Islamic leadership shapes a positive organizational culture characterized by ethical conduct and shared values. The findings also highlight that organizational culture plays a crucial mediating role, reinforcing the link between Islamic leadership and organizational commitment. Employees report higher satisfaction and loyalty levels by fostering a culture of shared values and collaboration. This study underscores the importance of integrating Islamic leadership principles into organizational practices to enhance employee performance and commitment. It provides valuable insights into the relationship between leadership, culture, and organizational goals, emphasizing how ethical values can create a sustainable and harmonious work environment.